Nypd red 6 eaudiobook - Patterson, James (NYPD Red, 2020)
In this heart-stopping thriller, a brazen kidnapper targets the most lavish New York City wedding of the season—and takes "Here Comes the Bride" as an invitation. Reality star Erin Easton's "Wedding of the Century" may have a cable crew documenting every extravagant bridal detail, but when "Airhead Easton" disappears from the reception, it's no diva turn. Her dressing room is empty but for a blood-spattered wedding gown and signs of a struggle. Detective Kylie MacDonald of NYPD Red, already on-scene as a plus-one, loops in her partner, Detective Zach Jordan to activate Level One mobilization for this PR nightmare. But when Erin's "proof of life" video makes it to air—rather than to evidence—every A-lister on the guest list becomes a target of suspicion . . . or just a target.